Physiological and metabolomic analysis reveals maturity stage-dependent nitrogen regulation of vitamin C content in pepper fruit - Zhang, Lu; Zhang, Fen; Wang, Yuan; Ma, Xiao; Shen, Yuanpeng; Wang, Xiaozhong; Yang, Huaiyu; Zhang, Wei; Lakshmanan, Prakash; Hu, Yuncai; Xu, Jiuliang; Chen, Xinping; et al. (Frontiers in Plant Science, 2023)
Pepper is one of the most vitamin C enriched vegetables worldwide. Although applying nitrogen (N) fertilizer is an important practice for high fruit yield in pepper production, it is still unclear how N application regulates pepper fruit vitamin C anabolism at different maturity stage. To further the understanding, we combined physiological and metabolomic analysis to investigate the fruit vitamin C content (including ascorbic acid (AsA) and dehydroascorbic acid (DHA)), related enzyme activity and non-targeted metabolites of field-grown chili pepper produced under different N levels at mature green and red stages. The results showed that increasing N application reduced AsA content in pepper fruit at both maturity stages, but highly elevated DHA content only at mature green stage. Regardless of N application level, AsA content displayed an increasing trend while DHA content was reduced as pepper fruit maturity advanced, resulting in a higher content of total vitamin C at the mature green stage. The L-galactose pathway, D-galacturonate pathway, and myo-inositol pathway were identified for AsA biosynthesis. The involved precursor metabolites were mainly negatively regulated by increasing N application, and their accumulation increased when pepper fruit developed from green to red stage. Meanwhile, the activities of key enzymes and metabolites in relation to degradation and recycling processes of AsA and DHA were increased or did not change with increasing N application, and they were differently influenced as fruit maturing. As a result, the recommended N application level (250 kg N ha-1) could maintain relatively high total vitamin C content in pepper fruits without yield loss at both maturity stages. These findings highlight the importance of optimizing N application level to maximize vitamin C content in pepper fruits, and provide a better understanding of the maturity stage-dependent N regulation on vitamin C anabolism.